Competitive analysis of tourist destinations in the Indonesia, Malaysia, Thailand Growth Triangle (IMT.GT) based on WTO indexes - Lebai Othman, Ismail; Mohd Ibrahim, Jaafar Ali; Ahmad, Norafifah; Abdul Jabbar, Hijattulah; Ismail, Aniz (2015)
Recently the notion and the measurement of destination competitiveness have garnered increasing attention in the economics literature on tourism. The reason for this interest emerges from both the increasing economic importance of the tourist sector and the increasing competition on the tourist market as a consequence of the transition from mass tourism to a new age of tourism that calls for a tailor-made approach to the specific attitudes and needs of tourists. This paper assesses the competitiveness of the travel and tourism industry in the IMT-GT region (Indonesia, Malaysia and Thailand) based on the methodology and the specific results provided in the Travel and Tourism Competitiveness Report 2013 and take into consideration the most representative performance indicators of this industry provided by the World Tourism Organization.The resulting Travel & Tourism Competitiveness Report is an accumulative report from the previous year‘s reports from 2007 until 2013 and contributes a platform for multi-stakeholder dialogue to ensure the development of strong and sustainable Travel and Tourism industries capable of contributing effectively to international economic development. The results of this study show that Malaysia is the leading country in all three subindexes which are Travel and Tourism Regulatory Framework (TTRF), Business Environment and Infrastructure (BEI) and Human, Cultural and Natural Resources (HCNR).Thailand is very strong in Travel Infrastructure followed by Malaysia and Indonesia, while Indonesia lies on the strength of its Natural Resources.Pearson correlation was used to measure the linear correlation between the overall competitiveness and all three subindexes.The results show that TTRF is the most significant factor in contributing to the overall competitiveness index.